The Integration of Building Information Modelling and Life Cycle Assessment: Progress, Challenges, Future Directions - Ting Pan; Péter Németh; Yee Van Fan; Ling Shao; Zekun Yang; Bohong Wang; Petar Sabev Varbanov (Chemical Engineering Transactions)
Building Information Modelling (BIM) plays a key role in the digitisation of the building sector, facilitating the design and construction of buildings. Environmental impacts have become an important factor to consider in building design and construction, often analysed through Life Cycle Assessment (LCA). The integration of BIM and LCA is crucial for supporting sustainable building design and construction. However, there is a lack of up-to-date reviews that consider the role of artificial intelligence (AI) in the integration of BIM and LCA. This paper addresses this gap by examining the recent progress, challenges, and future directions in building carbon emission accounting for buildings. The integration of the BIM-LCA for environmental impact accounting is explored, including goal and scope definition, life cycle inventory, impact assessment, interpretation, interoperability, and integration AI. The results identify gaps in BIM-LCA integration, including transparency issues and reliance on non-local databases. Future directions emphasise enhancing data quality, refining models, and developing AI methods for carbon emission predictions to explore decarbonisation strategy in the building sector. The review contributes to early-stage analysis, facilitating informed decision-making in sustainable building design and construction.